Top electrode dependent resistive switching in M/ZnO/ITO memristors, M = Al, ITO, Cu, and Au. (March 2022) - Praveen, P.; Rose, T. Priya; Saji, K.J.
Abstract: Resistive random access memory or memristive devices has emerged as a new paradigm for non-volatile memory and neuromorphic systems due to low power consumption, smaller footprint, and ultra-fast operation. This paper reports the dependency of top electrode on the resistive switching behavior of ZnO memristive devices. ZnO based memristor with ITO bottom electrode and Al, ITO, Cu or Au as top electrode were fabricated using room temperature radio frequency sputtering. Thickness of the ZnO layer was optimized for Al/ZnO/ITO device structure. Both filament type and interface type resistive switching mechanisms were observed in the devices by changing the top electrode material. Valance change mechanism (VCM) and electrochemical metallization (ECM) were observed in filament type resistive switching depending the type of the top electrode. Al, ITO, and Cu top electrode devices showed bipolar and filament type resistive switching. Unipolar and interface type resistive switching was realized in gold top electrode (Au/ZnO/ITO) device. The conduction mechanisms in these memristors were also investigated. Graphical abstract: Highlights: Top electrode (TE) dependent resistive switching (RS) in Metal/ZnO/ITO memristor. Filament type and interface type RS were achieved by changing TE material. VCM and ECM type conductive filaments were observed depending on TE. Charge conduction mechanisms were calculated for resistive switching devices.